Granice literatury, granice poetyki, granice granic dzisiaj. Jedno pytanie - Tenczyńska, Anna (Załącznik Kulturoznawczy, 2021)
The subject of reflection in the article Boundaries of Literature, Boundaries of Poetics, Boundaries of Boundaries Today. One Question is the place and role of poetics in contemporary Polish humanistic research. The author makes a short recapitulation of stages and themes of the ongoing discussion on the status of poetics (especially) in the last three decades, which, in her opinion, are particularly important. The widening of its boundaries, seen and significant for contemporary culture, prompts the author to ask about the extent to which the categories and tools of poetics are used in the contemporary Polish non-literary studies, on the example of the discourse of musicology.